2019
DOI: 10.1017/s0007114519000096
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nitrate consumption and risk of CHD in women from the Nurses’ Health Study

Abstract: The consumption of nitrate-rich vegetables can acutely lower blood pressure and improve mediators shown to optimise vascular health. However, we do not yet understand the impact of long-term habitual dietary nitrate intake and its association with CVD. Therefore, the aim of this investigation was to examine the relationship between habitual dietary nitrate intakes and risk of CHD in women from the Nurses’ Health Study. We prospectively followed 62 535 women who were free from diabetes, CVD and cancer at baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 59 publications
1
16
1
Order By: Relevance
“…The 53,150 Danish participants included in the present study had a median [IQR] age of 56 [52-60] years at entry and a median [IQR] follow-up of 21 [15][16][17][18][19][20][21][22] years. Total median [IQR] vegetable nitrate intake was 59 mg/day and non-vegetable nitrate intake was 15 mg/day [12][13][14][15][16][17][18]. Major individual vegetables that contributed to vegetable nitrate intake were lettuce (41%), potato (22%), celery (10%), carrot (5%), and spinach (3%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 53,150 Danish participants included in the present study had a median [IQR] age of 56 [52-60] years at entry and a median [IQR] follow-up of 21 [15][16][17][18][19][20][21][22] years. Total median [IQR] vegetable nitrate intake was 59 mg/day and non-vegetable nitrate intake was 15 mg/day [12][13][14][15][16][17][18]. Major individual vegetables that contributed to vegetable nitrate intake were lettuce (41%), potato (22%), celery (10%), carrot (5%), and spinach (3%).…”
Section: Resultsmentioning
confidence: 99%
“…However, evidence from observational studies of a reduction in CVD risk with habitual dietary nitrate intake is incomplete. Three Australian prospective studies (< 5500 participants and < 2000 incident cases each) have reported a lower risk of CVD [ 9 12 ], with higher dietary nitrate intakes while a large American prospective study (~ 60,000 participants; ~ 2300 incident cases) observed no benefit [ 13 ]. The established pathway via which dietary nitrate augments NO and accumulating evidence from clinical trials provides a strong rationale to further investigate the relationship between habitual dietary nitrate intake and risk of CVD in a large prospective study with a long follow-up, a large number of incident cases, and a comprehensive measure of nitrate intake.…”
Section: Introductionmentioning
confidence: 99%
“… Liu et al [ 108 ] 2900 Prospective (Blue Mountains Eye Study) 15 FFQ CVD mortality In multivariable-adjusted analysis, participants in quartile 4 [> 137.8 mg/d; HR 0.63 (95% CI 0.41, 0.95)] of vegetable NO 3 − intake had lower hazards for CVD mortality compared to participants in quartile 1 (< 69.5 mg/d) Mendy et al [ 109 ] 17,618 Prospective (NHANES) 4.3 Urinary NO 3 − in spot urine samples Hypertension and CVD prevalence and all-cause mortality 1-unit increase in log-transformed urinary NO 3 − was associated with a > 30% decrease in the odds of hypertension (odds ratio, 0.67; 95% confidence interval [CI], 0.55–0.81), stroke (OR, 0.61, 95% CI, 0.43–0.87) and cardiovascular mortality (HR, 0.44; 95% CI, 0.26–0.73) Jackson et al [ 110 ] 5324 Prospective (Australian Longitudinal Study on Women’s Health) 15 FFQ Incidence of self-reported CVD-related complications Women reporting higher total dietary NO 3 − intakes (Q4 > 78.2 mg/d) and vegetable NO 3 − intakes (Q4 > 64.4 mg/d) were 25 and 27% reduced risk of developing CVD-related complications, respectively. Jackson et al [ 111 ] Nurses’ Health Study and Health (62,535 women) Prospective 26 FFQ Coronary heart disease Dietary NO 3 − intake was not related to risk of CHD after adjustment for other lifestyle and non-vegetable dietary factors Sim et al [ 112 ] 1420 Cross-sectional (Perth Longitudinal Study of Aging in Women) FFQ Hand-grip strength and time up and go (TUG) Higher NO 3 − intake (31.2 mg/d) was associated with lower odds for weak grip strength (OR 0.84, 95% CI 0.74–0.95, P = 0.005) and slow TUG (OR 0.86, 95% CI 0.76–0.98, P = 0.021) Riddell et al [ 113 ] 2656 Prospective 1.5 Urinary NO 3 − to creatinine ratio (uNCR) Prediction of renal transplant rejection Overall uNCR was h...…”
Section: Main Textmentioning
confidence: 99%
“…The results showed a significantly lower risk of primary open-angle glaucoma in participants with higher NO 3 − intake [ 100 ]. However, a subsequent analysis conducted in the Nurses’ Health Study found a non-significant association between dietary NO 3 − and prospective risk of coronary heart disease [ 111 ]. More recently, several cross-sectional and longitudinal studies have observed significant associations between high NO 3 − intake or urinary NO 3 − concentrations (as a proxy for NO 3 − intake) with cardiovascular outcomes including lower BP [ 107 ], risk of hypertension [ 109 ], common carotid intimal medial thickness [ 103 ], congestive heart failure [ 114 ] and CVD mortality [ 109 ].…”
Section: Main Textmentioning
confidence: 99%
“…5,6 Studies in humans support preclinical findings, showing that the administration of these anions reduces blood pressure in both normotensive 7 and hypertensive individuals, 8,9 improves endothelial function, 9 protects against myocardial ischemia/reperfusion injury 10 and improves exercise performance. 11 Larger population studies looking at leafy green vegetables, which contain high amounts of nitrate, in relation to outcomes such as coronary heart disease, 12,13 type 2 diabetes 14 and all-course cardiovascular mortality 15,16 have suggested an inverse relationship.…”
Section: Introductionmentioning
confidence: 99%